PROSPECTS OF RESPONSIBLE TOURISM IN KERALA: EVIDENCE FROM KUMARAKAM IN KOTTAYAM DISTRICT - Manoj P. K. (International Journal of Research in Management & Social Science, 2015)
Responsible Tourism (RT) has got special significance in Kerala–the southernmost state in India with an enviable tourism infrastructure, often projected as ‘God’s own Country’. Taking the case of Kumarakam, one of the most prominent RT destinations in Kerala in the Kottayam district, this paper makes a case study of the RT initiatives of ‘Samrudhy’ group. Accordingly, the problems and prospects of RT are studied and suggestions are made for more effective functioning of their RT initiatives